URINARY HYDROXY-PROLINE ESTIMATION IS CHEAP BIOCHEMICAL MARKER OF BONE TURNOVER IN POST MENOPAUSAL WOMEN - Sabiullah, Mohammed; Suleman, Md Dawood; Rehmatunissa, Rehmatunissa; Ather, Md; Nasreen, Nasreen (Journal of Drug Delivery and Therapeutics, 2015)
Aim: To estimate urinary hydroxy- proline in pre and post menopausal  Women as a marker of bone resorption.Materials and methods: This is a prospective, observational  study of 25 healthy post menopausal women with 25 healthy premenopausal women as control conducted at Gandhi Hospital Secunderabad. The study period was between June 2008 to June 2010. 24 hours urinary Hydroxyproline  was measured in both cases and controls.Results: The mean urinary  Hydroxyproline in Post menopausal women was 31.64 with standard deviation of 3.37. The mean urinary Hydroxyproline in Pre menopausal women was 19.61 with standard deviation of 2.34. It has got the statistical significance with p value of